Movement Coordination: Identification of Development Peculiarities in Girls and Boys Aged 11-13 - O. Ivashchenko; O. Khudolii; S. Iermakov; P. Bartik; V. Prykhodko (OVS LLC, 2018)
The study objective is to determine the possibility of identifying the state of coordination abilities development in girls and boys aged 11-13 using the methodology of multidimensional statistics. Materials and methods: Study participants. The study involved girls: 11 (n=20), 12 (n=23), 13 (n=19) years old; boys: 11 (n=21), 12 (n=20), 13 (n=19) years old. Study organization. The paper used analysis and generalization of scientific literature data, testing, discriminant analysis. Testing procedure. The testing program included well-known tests (Liakh, 2000; Serhiienko, 2001; Ivashchenko, 2016). Study results: The first canonical function explains 65.7% of the results variation, the second one - 25.1%, the third - 4.8%, which indicates their informative value. The coefficients of canonical correlation indicate the prognostic value of these functions. The first canonical discriminant function is most substantially related to the results of tests 4 (r=0.526), 14 (r=0.377), 2 (r=-0.306): therefore, a significant difference between the girls and boys aged 11-13 is observed in the development level of relative and speed strength, movement coordination. The structure coefficients of the second canonical discriminant function indicate that the function is most substantially related to variables 2 (r=0.502), 16 (r=0.434), 9 (r=0.379), 17 (r=0.357): so, a significant difference between the girls aged 12-13 and boys aged 11-13 is observed in speed strength, vestibular stability, and anthropometric data. Conclusions: The discriminant models characterize both age- and gender-related peculiarities of movement coordination development in the girls and boys aged 11-13. The data obtained show significant differences between the groups of girls and boys aged 11-13 both in the structure of coordination abilities development and the level of preparedness, and highlight the need to conduct separate physical education classes for girls and boys. Different programs should be used to develop coordination abilities in boys and girls aged 11-13.